Constitucionalismo democrático: sobre constituição, presunção de inocência e execução provisória da pena - Ingrid Cunha Dantas (2018)
The proposed research seeks to analyze, in the light of the digressions of the Democratic Constitutionalism, the interpretations conferred to the principle of presumption of innocence, especially as far as its implications in the criminal procedural. The analysis, although not limited to judicial interpretation, has as its starting point the Supremo Tribunal Federal's views on the subject during the validity of the Constitution of 1988, especially its last, in 2016, in the judgment of HC 126.292/SP. In this case, the Court allowed the provisional execution of the penal sentence after second-degree conviction, mitigating the principle of presumption of innocence for a response to society. This analysis intends to rethink the role of the courts in the constitutional interpretation, going beyond juriscentric and normative theories that limit the process of interpreting the constitution to the activity developed by the judges. For this reason, the american approach is adopted, notably that developed by the Yale school theoreticians, which understands that along with the courts in constitutional interpretation, there are also other nonjudicial actors, among them the people, the political institutions and the government, equally legitimate and important members in the construction of the national political project. Therefore, we intend to develop a constitutional vision that "takes seriously" the fundamental commitments assumed with the 1988 Constitution, which, among its main objectives, sought to eradicate the instrumentalization of the individual, instituting democracy as a form of government to be opposed to dictatorial attempts to silence or oppress the "other", whoever that is.